(untitled) (Al-Academy, 2016)
This research deals with the nature of the aesthetic employment of wool in the Alfred Hitchcock films, as this director is characterized by rich his experience that dealt with the photo film days of silent film and managed efficiently in the construction of his films, as well as when the audio input The Hitchhiker employ sound aesthetic ways still emulated so far. So I rely researcher this subject and the division of research into four chapters, such as the first quarter included the methodological framework which dealt with the problem of research and the importance of research, and the goals of the research, as well as the limits of research and finally determine the terms.The second chapter includes theoretical framework and previous studies, where the researcher by dividing it into two sections dealt with the two search for a unique cinematic experiences Hitchcock as well as actors in his ways aesthetic Employment sound in all of his movies. In the end, without indications researcher discussed the results of a theoretical framework.Chapter III, action research, where the researcher will select two films of Hitchcock movies and are not birds and film rear window, and analyzed the sample is based on indicators that came out of the theoretical framework. Finally, in the fourth quarter researcher took a series of findings, conclusions and seal Find a range of sources